Do Conditional Cash Transfers Lead to Medium-Term Impacts? : Evidence from a Female School Stipend Program in Pakistan - Independent Evaluation Group (World Bank, Washington, DC, 2017)
Conditional cash transfer (CCT) programs are becoming a popular tool for alleviating short-term poverty and reducing the inter-generational transmission of poverty. More than 30 developing and transition countries have implemented these programs, providing incentives to poor households to make investments in the human capital of their children. Programs vary in scale, transfer size, conditionality's, eligibility, and implementation features. This report is structured around five chapters as follows: the first chapter gives an overview of the program, the context in which it was implemented and available evidence on the impacts of the Female School Stipend Program (FSSP) as well as other CCTs. Chapter two focuses on the questions this evaluation sets out to answer and the methods and information used to answer them. The third chapter presents the results from the analysis and is structured around three evaluation questions regarding average impact, heterogeneity of impacts, and spillover effects. Chapter four performs the robustness checks of the findings, examining whether they are sensitive to preprogram trends, measurement error, endogenous compositional changes, and crowding-out effects. Finally, the conclusion discusses the implications of the results, some limitations of this evaluation, and areas that require further work.